Conservancies, Conflict and Dispossession: The Winners and Losers of Oil Exploration in Turkana, Kenya. (5th December 2020) - Mkutu, Kennedy; Mdee, Anna
Abstract: Formerly marginal areas are increasingly the focus of extractive mega-projects, which are framed as necessary for economic growth and a modern industrial economy. Yet there are concerns that such projects are unjustly displacing local populations, facilitated through the alliances of local elites with foreign investors. This article asks, who are the winners and losers from oil exploration in the Turkana region of Kenya? Using longitudinal ethnographic research on the dynamics of local government, oil exploration, and pastoralist livelihoods in Turkana, Mkutu and Mdee highlight how current processes may exacerbate inequality and marginalization, with the potential for increasingly violent consequences.